On the systematic status of the genus Oriocalotes Günther, 1864 (Squamata: Agamidae: Draconinae) with the description of a new species from Mizoram state, Northeast India - Giri, Varad. B.; Chaitanya, R.; Mahony, Stephen; Lalrounga, Samuel; Lalrinchhana, C.; Das, Abhijit; Sarkar, Vivek; Karanth, Praveen; Deepak, V. (Zootaxa, 2019)
The montane agamid lizard genus Oriocalotes is currently considered monotypic, represented by the species, O. paulus. The systematic status of this taxon has remained questionable since its initial descriptions in the mid-1800s. A detailed molecular and morphological study was carried out to assess the validity of this genus, and its systematic position within the Asian agamid subfamily, Draconinae. Freshly collected and historical museum specimens from the type locality of O. paulus were examined morphologically, along with additional samples collected from localities in Mizoram state, Northeast India. Utilising newly generated molecular sequences (two mitochondrial and three nuclear genes), combined with those previously published for representative genera from the subfamilies Draconinae and Agaminae, Maximum Likelihood and Bayesian phylogenetic trees were constructed. Phylogenetic results suggest that Oriocalotes is part of the widespread South and Southeast Asian radiation of Calotes. Comparative morphological studies (including external morphology, hemipenis and osteology) between Oriocalotes and related genera further support this systematic placement. Oriocalotes is herein regarded as a junior subjective synonym of Calotes. Calotes paulus comb. nov. is also assigned a lectotype and given a detailed redescription based on the lectotype, paralectotypes and additional topotypic material. Furthermore, the specimens collected from Mizoram populations are found to be morphologically and genetically distinct from Calotes paulus comb. nov., and are described herein as a new species, Calotes zolaiking sp. nov.